PERBEDAAN MODEL PROBLEM BASED LEARNING DAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA - Anugrah Ronansa Ananda; Elly Sukmanasa; Rukmini Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine differences in learning outcomes of the Problem Based Learning and Project Based Learning models on mathematics learning outcomes. This research was carried out at SDN Julang, Bogor City, for the 2022/2023 school year. The research method used was a quasi-experimental design with 3 groups. The subjects of this study were fifth grade students at SDN Julang, Bogor, with a total of 75 students. Data collection was carried out to obtain learning outcomes obtained by using pretest and posttest. The researcher also conducted a normality test with the Lilliefors test for the three samples with normal distribution because the values ​​of the three samples were smaller than the Ltable. In the Problem Based Learning class group, the value of Lcount ≤ Ltable was obtained, namely 0.025 ≤ 0.173, in the Project Based Learning class group, the value of Lcount ≤ Ltable was obtained, namely 0.005 ≤ 0.173, and in the control class group, the value of Lcount ≤ Ltable was obtained, namely 0.052 ≤ 0.173. Then in the homogeneity test the data is homogeneous because it is smaller than X2 table, the value is 0.731 ≤ 5.991. Furthermore, in the hypothesis test, the tcount is 5.31 greater than the ttable of 2.0`603, indicating that H0 is rejected and Ha is accepted. Thus there are differences in learning outcomes of mathematics through Problem Based Learning, Project Based Learning, and Conventional models for fifth grade students at SDN Julang, Bogor City.